2018
DOI: 10.3390/healthcare6030097
|View full text |Cite
|
Sign up to set email alerts
|

Academic Palliative Care Research in Portugal: Are We on the Right Track?

Abstract: Background: The narrow link between practice, education, and research is essential to palliative care development. In Portugal, academic postgraduate publications are the main booster for palliative care research. Methods: This is a bibliometric study that aims to identify Portuguese palliative care postgraduate academic work published in electronic academic repositories between 2000 and 2015. Results: 488 publications were identified. The number of publications has increased, especially in the last five years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although the majority of palliative care research in Portugal is done to improve individual-level practice [31], there still is a lack of evidence regarding the healthcare received by adult individuals in the last months of life in this country. This review included eight quantitative descriptive retrospective studies and one quantitative comparative retrospective study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of palliative care research in Portugal is done to improve individual-level practice [31], there still is a lack of evidence regarding the healthcare received by adult individuals in the last months of life in this country. This review included eight quantitative descriptive retrospective studies and one quantitative comparative retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, most palliative care research is conducted during an academic course and as time can be a concern, researchers tend to choose contexts where data collection can be easier. The development of research in non-hospital settings is one of the major gaps in palliative care investigations in Portugal [31]. The care provided at the end of life has become an important issue in many countries [8,18].…”
Section: Discussionmentioning
confidence: 99%
“…This research model has not previously been introduced when taking into account the mediating role SE can play between AL and civility. Furthermore, the research contributes to the AL health-care literature as a new area of study (Laschinger et al , 2013; Malila et al , 2018), as well as to leadership literature in general, considering leadership studies in Portugal are not currently satisfactory as a body of literature of the overall scope (Pereira et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A recent bibliometric study regarding the postgraduate academic publications in Portugal in the field of palliative care over the past few years showed that few methodological studies were conducted in Portugal [17]. Methodological studies are important for the development of adequate measurement instruments to assess palliative care-related quality indicators [18].…”
Section: Introductionmentioning
confidence: 99%